Análise longitudinal do desempenho competitivo de duatletas medalhistas ao longo de uma temporada de 42 semanas - Tuono, A. T.; Pinheiro, A. M.; Gomes, A. C.; Padovani, C. R.; Borin, J. P. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2025)
Duathlon is a modality considered recent that consists of running-transition-cycling-transition-running and still lacks scientific informations about the competition system that helps in the preparation of athletes. Therefore, the objective was to analyze the competitive performance of duathletes based on anthropometric, neuromuscular and physiological indicators throughout six stages of the competition. For this purpose, seven male duathletes medalists in their respective categories (39.5 ± 4.9 years, 73.9 ± 8.7 kg and 63.7 ± 6.5 VO2max) who participated throughout the six stages in 42 week-season of the Interior Cup were analyzed. The following were analyzed total and partial time (hh:mm:ss), average speed (km/h), pace (mm:ss), body mass (kg), body fat (%), vertical jump (watts and cm), heart rate (bpm), lactate (mmol-L-1) in addition to geographic and climatic conditions. In the main results, there is a significant difference in the time and average speed throughout the six stages, with the best results in stages three and five (S3 and S5). The values of vertical jump are significantly lower after the race, while lactate concentration is significantly higher. It is hypothesized that this work may benefit coaches and duathletes from the characterization of the modality carried out through the analysis of long-term competitive performance that highlights the relevance of some particularities of the sprint duathlon, mainly regarding the importance of the calendar, regulations and rules of the competition, in addition to the influence of geographic and climatic conditions on the final performance of the athlete.